THE ANTIMICROBIAL ACTIVITY OF HONEY AND PROPOLIS AGAINST YEASTS CANDIDA SPECIES - MIROSLAVA KAČÁNIOVÁ (Scientific Papers Animal Science and Biotechnologies, 2009)
The aim of this study was to focus on the evaluation of the antimicrobial activity of honey samples and ethanolic extract of propolis (EEP) against Candida species. The honey concentrations - 50 % and 25 % of honey in distilled water were prepared. These preparations were tested for antimicrobial activity against five different types of yeasts: Candida crusei, Candida albicans, Candida (Torulopsis) glabrata, Candida parapsilosis and Candida tropicalis. The disc diffusion method using filter paper discs was employed. The antimicrobial activity was determined as an equivalent of the inhibition zones diameters (in millimeters) after incubation of the cultures for 48 hours. There were not seen an inhibition zones against the yeasts investigated in the 25 % and 50 % concentration of honey samples. The analysis among the tested yeasts showed that Candida crusei was the most sensitive in 70 % of EEP, and the sensitivity of the yeasts decreased in the order: Candida albicans > Candida parapsilosis > Candida tropicalis > Candida glabrata.